A cross-sectional analysis of zinc and copper levels and their relationship to cardiovascular disease risk markers in Qatar biobank participants - Kerkadi, Abdelhamid; Raïq, Hicham; Prince, Mohammad Shoaib; Bader, Loulia; Soltani, Abderrezzaq; Agouni, Abdelali (Frontiers in Cardiovascular Medicine, 2024)
Cardiovascular diseases (CVD) are the leading cause of mortality and morbidity worldwide.Dietary intake, particularly zinc (Zn) and copper (Cu) has been strongly associated with CVD.These trace elements play a crucial role in human enzyme activity, suppressing inflammation, catalyzing lipid metabolism enzymes, reducing oxidative stress, and regulating glucose metabolism. However, imbalances in these elements are linked to cardiovascular disturbances.Thus, this study aimed to investigate the association between circulating levels of Zn, Cu, and Zn/Cu ratio with CVD risk factors in the Qatari population.Bivariate logistic regression, adjusted for age, nationality, gender, and education was performed to examine the impact of Zn, Cu, and Zn/Cu ratio (as independent variables) on major CVD risk markers (as dependent variables). Participants in the highest Zn tertiles (T2 and T3) were at greater odds ratio (OR) of unfavorable metabolic functions such as elevated HbA1C [OR=2.5, p=0.015 (T2) and OR=3.2, p=0.002 (T3)], triglycerides [OR=2.17, p=0.015 (T2), and TyG index [OR=2.21, p=0.004 (T2), and OR=2.67, p < 0.001 (T3)] compared to T1. Conversely, they had significantly lower ORs for prolonged prothrombin time [OR=0.37, p=0.001 (T3)]. Higher levels of Cu (T2 and T3) had higher OR for elevated HDL-C levels [OR=1.69, p=0.046 (T2), and OR=2.27, p=0.002 (T3)] and lower OR for elevated levels of triglycerides (OR=0.4, p=0.009, T3), diastolic blood pressure [OR=0.41, p=0.024 (T2), and OR=0.47, p=0.049 (T3)], and creatinine kinase (OR=0.27, p=0.014, T3) compared to T1. Higher levels of Cu (T2 and T3) were associated with a higher risk for elevated fibrinogen levels [OR=3.1, p=0.035 (T2), and OR=5.04, p=0.002 (T3)]. Additionally, higher Zn/Cu ratio (T2 and T3) were associated with lower ORs for elevated fibrinogen levels [OR=0.3, p=0.005 (T2), and OR=0.27, p=0.005 (T3)] compared to T1, indicating a lower risk of developing CVD.The study reveals a link between Zn, Cu, and the Zn/Cu ratio and cardiovascular disease risk. A higher Zn/Cu ratio may protect against CVD, while elevated Cu levels are linked to obesity, fibrinogen levels, and HbA1C. Maintaining optimal levels of these trace elements, either through diet or supplementation, may help reduce CVD risk.